The subject, the symbolic and nature - Hudson, Peter (PINS-Psychology in Society, 2018)
This article identifies the standard conception of the relationship between Nature and the Symbolic and contrasts it with that developed by the neuro-sciences, epigenetics and psychoanalysis. These latter develop a conception of nature as neither a self-sufficient totality that renders the human sciences redundant, nor as the merely passive substrate of the Symbolic. Here Nature requires “completion” by the Symbolic and vice-versa. In conclusion, the implications of this new articulation (of Nature and the Symbolic) for the status of the subject are addressed.